PENGOLAHAN CRUDE PALM OIL (CPO) MENJADI MINYAK SAWIT MERAH (MSM) MENGGUNAKAN FILTER BATUAN ZEOLIT, MEMBRAN KERAMIK DAN CARTRIDGE FILTER: PENGOLAHAN CRUDE PALM OIL (CPO) MENJADI MINYAK SAWIT MERAH (MSM) MENGGUNAKAN FILTER BATUAN ZEOLIT, MEMBRAN KERAMIK DAN CARTRIDGE FILTER - Yudis Afrizal; Erwana Dewi; Mustain Zamhari (KINETIKA, 2022)
In the manufacture of red palm oil using zeolite rock filtration, ceramic membranes and cartridge filters.Natural zeolite that can separate two or more phases of substances by using a porous ceramic membrane which is intended to separate the particles in Crude Palm Oil later. In the design of supporting tools in the manufacture of red palm oil using ceramic membrane filtration and Zeolite rocks include: CPO Filter, Stirrer, Coagulator, Stove, Circulation Pump, Zeolite Rock, Ceramic Membrane, Filter Cartridge, and Red Palm Oil Product Tank. For the treatment in this experiment, 0.1 ml of sulfuric acid and 250 ml of sodium hydroxide were added as degumming and neutralization with variations in time (2, 4, 6 minutes) and temperature (40℃, 60℃ and 80℃) with an operating pressure of 5 bar. In the results of red palm oil products, it was found that the Fatty Acids free and the peroxide value exceeds the standard of red palm oil sold in the market. The effect of the flux obtained decreases because the pores in the ceramic membrane begin to become clogged so that the volume of permeate that comes out of the oil sample decreases. The rejection obtained in this study made the rejection data increase and the beta carotene produced decreased. The results showed that the temperature of 60℃ is the optimum temperature in red palm oil research.